2012
DOI: 10.1186/1756-0500-5-305
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-child transmission of HIV: the pre-rapid advice experience of the university of Nigeria teaching hospital Ituku/Ozalla, Enugu, South-east Nigeria

Abstract: Background Mother-to-child transmission of human immune deficiency virus (HIV) is the most common route of HIV transmission in the pediatric age group. A number of risk factors contribute to the rate of this transmission. Such risk factors include advance maternal HIV disease, lack of anti-viral prophylaxis in the mother and child, mixing of maternal and infant blood during delivery and breastfeeding. This study aims to determine the cumulative HIV infection rate by 18 months and the associated ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In that study, blood transfusion accounted for as much as 68% of the pediatric HIV infection. Our current study supports the new thinking that eliminating paediatric HIV will therefore require strengthening interventions that reduces MTCT of HIV [12,13].…”
Section: Discussionsupporting
confidence: 79%
“…In that study, blood transfusion accounted for as much as 68% of the pediatric HIV infection. Our current study supports the new thinking that eliminating paediatric HIV will therefore require strengthening interventions that reduces MTCT of HIV [12,13].…”
Section: Discussionsupporting
confidence: 79%
“…The study of Ngozi et al showed that holistic but cost effective preventive interventions help in reducing the rate of mother-to-child transmission of HIV even in economically-developing settings [23]. Turan et al found that PMTCT of HIV and antenatal care integration in pregnancy might improve the implementation and effectiveness of PMTCT in rural area [24].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Tudor et al describes, for example, that integrated PMTCT services could effectively reduce mother-to-child transmission of HIV [33]. Ibeziako et al have shown that holistic but cost-effective prevention interventions help reduce the rate of mother-to-child transmission of HIV, even in economically developing countries [34]. These measures will achieve a reduction or even eradication of mother-to-child transmission of HIV [35].…”
Section: Discussionmentioning
confidence: 99%